Penciptaan Karya Mannequin Puppet "Asmara Samara" - Asmara Nata, I Wayan Candra; Marajaya, I Made; Sekar Marhaeni, Ni Komang; Darma Putra, I Gusti Made (JURNAL DAMAR PEDALANGAN, 2025)
The creation of the Mannequin Puppet performance entitled Asmara Samara is driven by the need for innovation in Balinese puppetry to bridge traditional values with contemporary artistic expression. This work presents a tragic romance between Prince Semara Yana of the Nila Kingdom and Princess Asmara Gantari of the Seta Kingdom, whose love is challenged by an enduring conflict between their parents. The purpose of this artistic project is to introduce a new format of puppetry that is communicative, philosophically grounded, and appealing to younger generations. The creative process employed the Dalang Anumana method formulated by I Gusti Made Darma Putra, consisting of five stages: Ngawit (starting), Ngepah (conception), Ngastawa (spirituality), Ngripta (making), and Ngebah (performing). Through visual exploration, media experimentation, and integration of theater, dance, and video mapping, the performance successfully embodies Balinese aesthetics within a naturalistic and symbolic style. The result demonstrates how Balinese philosophical concepts such as swasraya, karmaphala, and tri hita karana can be recontextualized through innovative performance media. In conclusion, Asmara Samara not only represents an artistic innovation but also serves as a medium for the preservation and transformation of Balinese puppetry in the global cultural landscape.